Two new species of Atatina earthworm (Rhinodrilidae, Clitellata) from the Gurupi Biological Reserve, Maranhão, Brazil - Hernández-García, Luis Manuel; Rodríguez, Giovanny Angiolillo; James, Samuel Wooster; Limeira-De-Oliveira, Francisco; Rousseau, Guillaume Xavier (Zootaxa, 2024)
Only three species of the Atatina genus had been reported, both living distant one of another in the Amazon. Here we reported two new species for the genus living in remnant forest of the Gurupi Biological Reserve. Atatina arimikuriaka sp. nov. with three pairs of spermathecae, prostomium tentacular, and annular clitellum while Atatina arimikuritea sp. nov. has only one pair of spermathecae in IX, annular clitellum, and a smallest tubercula pubertatis. The two species are unique because the annular clitellum is contrasting with the saddle-shaped of other species.